Effects of solar tracking on different types of solar panels; experimental study for thermal and photovoltaic types - Akpinar, Ebru; Katircioglu, Gizem Gul; Das, Mehmet (Pergamon-Elsevier Science Ltd, 2025)
Renewable energy sources are sustainable and environmentally friendly sources and are used in many fields. Especially the production of hot fluid and electrical energy with solar panels is increasing daily. Due to the varying incidence angles and capacities of the sun's rays, many technological methods are applied to achieve maximum efficiency in the panels. Solar tracking systems are the most popular of these methods. Solar tracking systems ensure that the sun rays coming to the surface of the solar collectors are perpendicular during the sunshine period, and thus, maximum efficiency is achieved. This study investigates the effects of solar tracking system studies in the literature on the performance of different types of solar panels. Furthermore, the effects of the solar tracking system on the performance of solar air collectors (SAC), monocrystalline photovoltaic (MPV), and polycrystalline photovoltaic (PPV) panels are experimentally investigated. In this context, an experimental setup was designed and fabricated, and all panels were placed on a platform with sun-tracking capability. Tests were carried out under the same environmental conditions in the solar tracking system's stationary and active (moving) conditions. As a result of the tests, the energy efficiency of the SAC with solar tracking increased by 75.2% compared to the fixed system. In addition, the moving SAC output temperature increased by 25.6% compared to the fixed SAC output temperature. With the solar tracking system in photovoltaic solar panels, the electrical power generation values of MPV and PPV solar panels increased by 19.1% and 26.3%, respectively. As a result of the tests, it was observed that the performance increase of photovoltaic panels with the same surface area was higher than SAC. In addition, the solar tracking system increased the surface temperature of MPV and PPV panels by an average of 11.7% and 17%, respectively. The results support the idea that solar tracking systems should be widely used in photovoltaic technologies.
Keywords: Solar energy; Thermal solar panel; Photovoltaic solar panel; Solar tracking; Energy